The design patterns companion - Bain, Scott L. (Project Management Institute, Inc., 2020)
"Design patterns are not merely "reusable solutions." Rather, they offer a language of design; a way for developers to communicate, collaborate, and make collective decisions about design. When you study design patterns, you are teaching yourself about what a good design is, and why-they represent and exemplify good principles and stong practices. This book is meant to be a go-to field guide or handbook for practitioners"--